Baseball game. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Evacuees playing baseball at Portland Assembly Center in Oregon. The Portland Assembly Center was formerly known as the North Portland International Livestock Exposition Center.